Seeking Opportunities: Migration as an Income Diversification Strategy of Households in Kakamega District in Kenya - Lena Giesbert (German Institute of Global and Area Studies (GIGA), 2007)
Migration and remittances are widely seen as major components of diversification strategies aimed at coping with risky environments in developing countries. The debate in the literature mainly concentrates on effects of and access to the strategy of migration. Against this background, the paper investigates patterns, determinants and the impact of internal migration on households based on data from a densely populated rural area in Western Kenya. The motivation behind migration is largely economic in kind. Accordingly, remittances account for a substantial share of household incomes. Results derived from a probit model estimation indicate that the likelihood of migration is independent from the wealth position of households. Instead, demographic household factors, education-related variables and migrant networks are of central importance. Migration and remittances are obviously more easily accessible than other opportunities of income diversification beyond farming for households across all levels of wealth, including the poorest households. – – Migration und damit verbundene remittances werden weithin als wesentliche Bestandteile von Diversifizierungsstrategien betrachtet, die von Haushalten in Entwicklungsländern zur Bewältigung von Risiken angewendet werden. Im Mittelpunkt der wissenschaftlichen Diskussion stehen dabei die Auswirkungen und der Zugang zu Migration und remittances. Vor diesem Hintergrund untersucht die Studie die Muster, Bestimmungsfaktoren und Auswirkungen von Migration auf die Haushalte der Migranten im Distrikt Kakamega, einem stark bevölkerten ländlichen Gebiet Westkenias. Die Motivation zur Migration ist hauptsächlich ökonomischer Art. Dementsprechend machen remittances einen hohen Anteil an den Einkommen der Empfängerhaushalte aus. Die Ergebnisse der Schätzungen des für die Analyse verwendeten Probit-Modells deuten darauf hin, dass die Wahrscheinlichkeit von Migration unabhängig von der Wohlstandsposition der Haushalte ist. Von hoher Bedeutung sind dagegen demographische und bildungsbezogene Faktoren sowie die Existenz von Migrantennetzwerken. Migration (und remittances) sind offenbar für Haushalte aller Einkommensschichten, einschließlich der ärmsten Haushalte, leichter zugänglich als andere Strategien der Einkommensdiversifizierung in nicht-landwirtschaftliche Aktivitäten.
Keywords: R23; Q12; D13; 330; migration; remittances; income diversification; coping strategies; sub-Saharan Africa; Kenya; Internationale Wanderung; Rücküberweisung (Migranten); Einkommensverteilung; Privater Haushalt; Kenia